A New Real Time Control Approach for Time Efficiency in Group Elevator Control System - BAYĞIN, Mehmet; ORHAN, Dilbirin; YAMAN, Orhan; KARAKÖSE, Mehmet (International Journal of Intelligent Systems and Applications in Engineering, 2016)
In parallel with the increase seen in the number of high-rise buildings, vertical transport systems are progressing. One of the results of this progress is the emergence of group elevator systems and their primary aim is to transport its passengers to the target floor the fastest way possible. Studies on this field are generally simulation and optimization based and they have an aim of minimizing the passengers’ waiting and traveling periods. In this study, a real time group elevator experimental setup was created and an optimization algorithm was applied on the setup. Genetic algorithm was chosen as optimization algorithm and this method was tested in an elevator prototype of 10 floors and 5 cabins. The results obtained revealed efficiency, performance and accuracy of proposed method.